1997
DOI: 10.1523/jneurosci.17-10-03401.1997
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaSerotonin Transporters Have Voltage-Dependent Uptake Coupled to a Serotonin-Gated Ion Channel

Abstract: Serotonin (5HT ) transporters (SERTs) couple to existing ion gradients to transport 5HT into presynaptic terminals. In mammalian SERTs, the transport cycle is reported as electroneutral, with a translocation of zero net charge, and 5HT uptake is independent of membrane voltage. Yet mammalian SERTs exhibit 5HT-induced currents, and Drosophila SERTs (dSERTs) show voltage-dependent uptake. Thus, the relationship between uptake and current remains controversial; furthermore, the number of 5HT molecules translocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
82
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 33 publications
12
82
0
Order By: Relevance
“…Monoamine transporters, as well as other family members, are regulated by phosphorylation and dephosphorylation by protein kinases and phosphatases. This subject was discussed recently in an excellent review and will not be covered in this review (see Blakely et a!., 1997).…”
Section: Monoamine Transportersmentioning
confidence: 99%
See 3 more Smart Citations
“…Monoamine transporters, as well as other family members, are regulated by phosphorylation and dephosphorylation by protein kinases and phosphatases. This subject was discussed recently in an excellent review and will not be covered in this review (see Blakely et a!., 1997).…”
Section: Monoamine Transportersmentioning
confidence: 99%
“…It was demonstrated that transporters may be involved in the action of numerous drugs and specific toxins that affect the nervous system (Snyder and D'Amato, 1986;Bergman et al, 1989;Kuhar et al, 1991). Monoamine transporters, for example, are targeted by major classes of antidepressants, psychostimulants, and antihypertensive drugs (Blakely et al, 1997). They are also necessary for the actions of several classes of neurotoxins that selectively poison specific neuronal targets (Snyder and D'Amato, 1986).…”
Section: Transporters As Pharmacological Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…An internal K ϩ ion is bound and countertransported, after dissociation of 5-HT, Na ϩ , and Cl Ϫ , as SERT returns to its initial state (8). Although the stoichiometry of 5-HT transport predicts an electroneutral process, electrophysiological studies have revealed a net inward current, which probably arises from an uncoupled excess inward flux of Na ϩ ions (9,10).…”
mentioning
confidence: 99%